Colonization of vines by Petri disease fungi, susceptibility of rootstocks to Phaeomoniella chlamydospora and their disinfection - Ferreira, Ana Beatriz Monteiro; Leite, Luís Garrigós; Hernandes, José Luiz; Harakava, Ricardo; Padovani, Carlos Roberto [UNESP]; Bueno, César Junior (Instituto Biológico, 2018)
Petri disease is complex, attacks young vine plants and it is difficult to be controlled. The fungus Phaeomoniella chlamydospora (Phc) has been identified as the main causative agent of this disease. This study aimed to evaluate the prevalent colonization of the Petri disease fungi in different portions of vine plants; to assess the susceptibility of grapevine rootstocks to the fungus P. chlamydospora; to assess the effect of solarization and biofumigation, followed by hot-water treatment (HWT), on the disinfection of cuttings of the rootstock IAC 766 infected with P. chlamydospora, and assess the effect of solarization and biofumigation, followed by HWT, on the rooting of cuttings of the rootstock IAC 766. For the prevalent colonization test, the fungus species detected and identified in ‘Niagara Rosada’ grafted on two rootstocks different were Phc and Phialemoniopsis ocularis. This is the first report of P. ocularis in a young vineyard in Brazil. Both fungi, in particular Phc, colonized only the plant’s basal part, drawing attention to the rootstock as target for control measures. Measurement of the dark streaks in the vascular system revealed that Golia was the least susceptible rootstock, and IAC 572 was the most susceptible to Phc. Moreover, biofumigation or temperature of 37°C applied for 7 and 14 days, both followed by HWT, suppressed Phc in cuttings of the rootstock IAC 766 without hampering their rooting. Meanwhile, new studies are needed to validate the efficiency of these disinfection techniques.

A doença de Petri é complexa, ataca plantas jovens de videira e é difícil de ser controlada. O fungo Phaeomoniella chlamydospora é o principal agente causal dessa doença. Os objetivos deste estudo foram: avaliar o local prevalente dos fungos da doença de Petri, em diferentes partes de plantas de videira; avaliar a suscetibilidade de porta-enxertos de videira para o fungo P. chlamydospora; avaliar o efeito da solarização e da biofumigação seguido de tratamento com água quente sobre a desinfecção de estacas do porta-enxerto IAC 766 infectadas com o fungo P. chlamydospora; avaliar o efeito da solarização e da biofumigação seguido de tratamento com água quente sobre o enraizamento de estacas do porta-enxerto IAC 766. Para o teste de colonização, as espécies de fungos detectadas e identificadas em Niagara Rosada enxertada em dois porta-enxertos diferentes foram P. chlamydospora e Phialemoniopsis ocularis. Este é o primeiro relato de P. ocularis em parrerais jovens de videira no Brasil. Ambos os fungos, em particular P. chlamydospora, colonizaram somente a parte basal das plantas, destacando-se os porta-enxertos como foco para medidas de controle. Medidas das estrias escuras no sistema vascular revelaram que Golia foi o porta-enxerto menos suscetível, e o IAC 572 foi o mais suscetíveis para P. chlamydospora. Além disso, a biofumigação ou a temperatura de 37ºC aplicadas por 7 e 14 dias seguidas de tratamento com água quente eliminaram P. chlamydospora em estacas do porta-enxerto IAC 766 sem afetar o enraizamento. No entanto, novos estudos são necessários ainda para validar a eficiência dessas técnicas de desinfecção.
Colonização de videiras pelos fungos da doença de Petri, suscetibilidade de porta-enxertos ao fungo Phaeomoniella chlamydospora e sua desinfecção
Keywords: Petri disease; propagating material; control; resistance; Vitis L; doença de Petri; material de propagação; controle; resistência; Vitis L